Effect of different prophylactical doses of ondansetron for the hemodynamic stability in patients undergoing cesarean section: a randomized controlled study - Qin, Rui; Xu, Xiangzhao; Zhao, Na; Shi, Yongqiang; Chen, Yi; Chen, Jinhua; Ni, Xinli (Frontiers in Medicine, 2025)
Background5-hydroxytryptamine 3 (5-HT3) receptor antagonists have been reported to reduce post-spinal anesthesia hypotension, though their efficacy remains controversial. We investigated the effect of prophylactic ondansetron on hemodynamic stability in patients undergoing cesarean section following spinal anesthesia.MethodsPatients scheduled for elective cesarean section (n = 120) were randomly allocated to three groups (NS group, 4 mg group, 8 mg group) of 40: those given 4 mL of normal saline (NS), and those given either 4 mg or 8 mg ondansetron (4 mL) before spinal anesthesia. Patient information, maternal systolic blood pressure stability [median performance error (MDPE), median absolute performance error (MDAPE)], the incidence of post-spinal anesthesia hypotension, norepinephrine doses, other adverse events (severe post-spinal anesthesia hypotension, nausea, vomiting, bradycardia, and hypertension), umbilical artery blood gas values, and infant Apgar scores were all recorded.ResultsThe primary outcomes (median performance error, MDPE and median absolute performance error, MDAPE) were significantly different among the three groups. (p = 0.001, p = 0.002). Compared with the NS group, systolic blood pressure (SBP) was maintained closer to baseline in the 4 mg group (p = 0.003, p = 0.006), as was the 8 mg group (p = 0.011, p = 0.006). There was a significant difference in the incidence of post-spinal anesthesia hypotension among the three groups (p = 0.002). However, only there was a statistical difference between NS and the 8 mg groups in pairwise comparisons (p = 0.001). The doses of norepinephrine, the incidences of other adverse events, umbilical artery blood gas, and Apgar scores were not statistically different between the three groups.ConclusionProphylactic 4 mg or 8 mg ondansetron improved hemodynamic stability after spinal anesthesia in cesarean section; however, only 8 mg reduced post-spinal anesthesia hypotension.Clinical trial registrationClinicaltrials.gov, NCT05475873.